Emotional States and the Portrayal of Psychoanalytic Conflicts in the Song Watch the World Burn by Falling in Reverse - Illahi, Ridho; Priyoto, priyoto; Herlyna, Herlyna (STIBA IEC JAKARTA, 2025)
The song Watch the World Burn by Falling in Reverse expresses the emotional and psychological struggles of the artist, who grapples with trauma, depression, and internal conflict as conveyed through the lyrics. This study aims to analyze the emotional states and psychoanalytic conflicts portrayed in the song. Using a qualitative descriptive method with content analysis techniques, the data were obtained from the song’s lyrics and examined through the lens of Freud’s psychoanalytic theory and literary psychology. The analysis classified the psychological expressions into themes of trauma, defense mechanisms such as repression, projection and sublimation, and the tension between primal impulses and social constraints. The results reveal that the lyrics articulate complex psychological conflicts and emotional states through rich metaphor and symbolism. This study highlights the role of contemporary song lyrics as a medium for psychological expression and contributes to literary psychology by deepening the understanding of how artists convey unconscious conflicts in their work.